Explaining superior returns in alternative energy investments using market-to-reinvestment ratio in an augmented fama-French model. - Sim, Sze Xiong. (2011)
Investments in alternative energy stocks have gained momentum in recent years given the greater public awareness of climate change brought on by increasing energy generation and depletion of fossil fuel resources. Our study finds that alternative energy investments result in significant superior returns as compared to that of the global stock market. In addition, we show that financial metrics such as beta, market capitalization and Price-to-Book ratio together with Market-to-Reinvestment ratio explains the superior returns of alternative energy stocks. This suggests the Market-to-Reinvestment ratio (defined as stock market capitalization divided by the sum of Capex and R&D expenditure) is a suitable proxy for investors’ and management’s confidence in reinvestment commitment made by alternative energy firms in maximising shareholder value.